Inside Back Cover: Tuning Optical Properties of Encapsulated Clusters of Gold Nanoparticles through Stimuli‐Triggered Controlled Aggregation (Chem. Eur. J. 23/2016). Issue 23 (17th May 2016) - Dergunov, Sergey A.; Kim, Mariya D.; Shmakov, Sergey N.; Richter, Andrew G.; Weigand, Steven; Pinkhassik, Eugene
Abstract : The image illustrates the change in optical properties of nanoparticles caused by externally triggered aggregation inside porous nanocapsules. Small nanoparticles that might be safe for biomedical applications often do not exhibit desirable optical characteristics. Aggregation of nanoparticles may produce suitable optical properties; however, controlling the size of aggregates is particularly difficult. This work addresses the challenge by entrapping groups of nanoparticles in porous polymer nanocapsules. Capsules with semi‐permeable shells permit communication with the environment while limiting the size of the aggregates of nanoparticles. More information can be found in the Communication by E. Pinkhassik, et al. onpage 7702 ff.